PENENTUAN PROFITABILITAS KOPERASI MELALUI EFISIENSI MODAL KERJA DAN EFEKTIVITAS PENGENDALIAN BIAYA - Ariyanti, Mrs.; Indriasih, Dewi; Tabrani, Mr. (PERMANA, 2016)
This study is aimed to analyze the efficiency of working capital and the effectiveness of cost control on probability. Population and sample in this research is Financial statement of PKP-RI Tegal City in 2012-2016. The Collection data in this study is quantitative. Sources of data in this study is secondary data which is obtained from financial statements PKP-RI Tegal city in 2012-2016. The Data collection technique in this research is documentations. Data analysis method use Trend analysis. The result indicate that the working capital efficiency is descreased, the working capital rotation was only 0,49% in 2013 mean while the lowest working capital rotation in 2016 was 0,29% this had impact on the low profitability level meanwhile the effectiveness of cost control also descreased but it is not significant. At the level of profitability of PKP-RI Tegal City also get fluctuations, the highest profitability level in 2012 is 2,02% meanwhile the lowest is in 2013 at 1,43 and it is still below the standard. Keywords: Working Capital; Cost Control; Profitability